Zalog pri Verdu = Zalog near Verd Tabor kamenodobnih lovcev na zahodnem robu Ljubljanskega barja = Stone Age hunters' camp at the western edge of the Ljubljansko barje - Gaspari, Andrej (Opera Instituti Archaeologici Sloveniae, 2006)
The Ljubljanica River with its tributaries has witnessed no less than a quarter of a century of organised underwater research. The latter has shown that the archaeological complex there unquestionably ranks among the most interesting ones in Slovenia with the finds from the beds and banks of the waterways speaking of nearby settlements, cemeteries, forts, control points or places of cult.These, together with various types of river vessels and other traces of water exploitation, improve in many ways the knowledge of the phenomenon that is the Ljubljansko barje as a cultural landscape as well as its specific dynamics closely related to the natural changes in the environment from the early periods of the prehistory onwards.